Lightweight kiln tools and their manufacturing method

The lightweight kiln tool addresses corrosion and thermal shock issues by using a specific composition and manufacturing method, ensuring high strength and efficiency in heat treatment processes.

JP7602892B2Active Publication Date: 2024-12-19ISOLITE INSULATING PROD CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2020179534
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-10-27
Publication Date
2024-12-19
Estimated Expiration
2040-10-27

AI Technical Summary

Technical Problem

Existing kiln tools for heat treating positive electrode materials in lithium ion secondary batteries face issues with corrosion resistance, thermal shock resistance, and mechanical strength due to high bulk specific gravity, leading to increased energy consumption and frequent roller replacement.

Method used

A lightweight kiln tool with a bulk specific gravity of 0.5 to 1.5, featuring a main body and protective layer composed of materials with low reactivity and controlled thermal expansion coefficients, porosity, and a manufacturing method that includes dry pressure molding to ensure adhesion and strength.

Benefits of technology

The solution provides a high-strength, lightweight kiln tool with excellent corrosion resistance and thermal shock resistance, reducing energy consumption and extending tool life while maintaining mechanical integrity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007602892000001
    Figure 0007602892000001
  • Figure 0007602892000002
    Figure 0007602892000002
  • Figure 0007602892000003
    Figure 0007602892000003
Patent Text Reader

Abstract

To provide a lightweight kiln-utensil of excellent corrosion resistance and high strength, and a method of producing the same.SOLUTION: The lightweight kiln-utensil of a bulk density of 0.5 to 1.5, constituted of a body section storing or holding a positive electrode material for use in a secondary lithium ion battery upon heat-treating the positive electrode material and of a protective layer provided on the face of the body section at least contacting the positive electrode material, is characterized in that the upper limit of the porosity of the body section is 80 vol.%, the protective layer comprises at least one species of a mineral composition selected from corundum, mullite, eucryptite, lithium aluminate, spodumene, spinel, zirconia, periclase, enstatite, and forsterite, the thermal expansion coefficient of the protective layer at a temperature of from a room temperature to 1000°C is 10×10-6 / K or lower and is in a range of 1.0 to 2.0 times of the thermal expansion coefficient of the body section, and the upper limit of the porosity of the protective layer is 50 vol.%.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to lightweight kiln furniture with excellent corrosion resistance and strength, which is used when heat treating positive electrode materials for lithium ion secondary batteries, and a method for manufacturing the same. [Background technology]

[0002] The positive electrode active material of a lithium-ion secondary battery is produced by charging powdered raw materials consisting of lithium-containing compounds, cobalt-containing compounds, manganese-containing compounds, nickel-containing compounds, iron-containing compounds, etc. into a heat treatment furnace and sintering them under predetermined heat treatment conditions. For this sintering process, ceramic kiln tools for containing or placing the powdered raw materials are widely used, including containers such as crucibles and saggers, and setters such as shelves and floor plates.

[0003] These kiln furniture are required to have corrosion resistance in order to prevent deterioration due to erosion caused by alkaline components such as lithium generated from the powdered raw materials to be fired during the firing process. After the firing process, the kiln furniture and its contents are rapidly cooled by forcibly cooling the temperature inside the heat treatment furnace by blowing air into the furnace to shorten the temperature drop time and increase the production efficiency. Therefore, the kiln furniture is also required to have thermal shock resistance. In addition, it is generally desirable for the kiln furniture to have a bending strength of 3 MPa or more.

[0004] For this reason, materials with a dense bulk density exceeding 1.5 are generally used for kiln furniture, and materials with a bulk density of about 2.0 are sometimes used. When the bulk density exceeds 1.5, the kiln furniture itself becomes heavy, and when the material to be fired is stored or placed on it, it becomes even heavier, so the load on the rollers for transporting the kiln furniture equipped in the kiln can become too large. As a result, problems such as bending, wear, and breakage of the rollers are likely to occur, and the rollers need to be replaced frequently. In addition, as the bulk density increases, the heat capacity also increases, so a lot of energy and time are required to heat and cool the kiln furniture, which is not preferable from the viewpoint of energy saving and manufacturing efficiency.

[0005] Therefore, it is possible to use materials with a low bulk density for kiln furniture. By reducing the bulk density, the heat capacity can be reduced and the thermal shock resistance can be increased. However, in this case, the porosity increases, which can lead to corrosion by alkaline components such as lithium and to a decrease in the mechanical strength of the structure. As a countermeasure, a technology has been proposed to improve the corrosion resistance of kiln furniture against alkaline components by coating the surfaces of kiln furniture containing materials such as spinel and alumina using basic materials.

[0006] For example, Patent Document 1 proposes a technique for forming a protective layer by coating a kiln tool body made of mullite or cordierite, which has a low bulk density, with one or more metal oxide materials such as zirconia, alumina, and magnesia, which are less reactive with the raw materials of lithium-ion secondary batteries. Patent Document 2 also proposes a technique for forming a protective layer by coating the surface of the kiln tool body with a material in which either or both of a metal oxide and a metal salt, which have a positive thermal expansion coefficient, and LiAlSiO4, which has a negative thermal expansion coefficient, are mixed in a predetermined ratio.

[0007] Furthermore, various methods have been proposed for forming a protective layer on the surface of the kiln tool body. For example, Patent Document 3 proposes a technique for forming a protective layer by spray coating the surface of the kiln tool with a material that is less reactive with the object to be fired. Patent Document 4 also proposes a technique for forming a protective layer made of a material that is less reactive with the object to be fired on the surface of the kiln tool using a secondary pressing method. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] JP 2014-118339 A [Patent Document 2] JP 2019-121601 A [Patent Document 3] JP 2002-154884 A [Patent Document 4] China Patent Application Publication No. 103311498 Summary of the Invention [Problem to be solved by the invention]

[0009] However, the metal oxides exemplified in Patent Document 1 have a larger positive thermal expansion coefficient than the kiln tool itself, so the protective layer made of the metal oxide is prone to cracking, and may peel off if used continuously. With the technology of Patent Document 2, depending on the thermal expansion coefficient of the kiln tool itself, the protective layer may peel off over a long period of repeated use. Also, if the protective layer has a high porosity or is thin, erosion may occur.

[0010] The method of Patent Document 3 has the problem that after the coating process is applied to the kiln tool body formed by firing, a heat treatment consisting of drying and firing must be performed again, which increases the number of manufacturing steps and increases the manufacturing cost. The technology of Patent Document 4 has the advantage that the thickness of the coating layer can be made thicker, but has the problem of a high bulk density. The present invention has been made in consideration of the problems of the above-mentioned conventional technologies, and aims to provide a kiln tool that is highly strong and lightweight with excellent corrosion resistance and is used in the heat treatment of the positive electrode material of a lithium-ion secondary battery, and a manufacturing method thereof. [Means for solving the problem]

[0011] In order to achieve the above object, the lightweight kiln furniture of the present invention is a lightweight kiln furniture having a bulk specific gravity of 0.5 to 1.5, the lightweight kiln furniture being composed of a main body for accommodating or placing a positive electrode material for a lithium ion secondary battery during heat treatment of the positive electrode material, and a protective layer provided on at least the surface of the main body that contacts the positive electrode material, the main body having an upper limit of porosity of 80 volume %, the protective layer having one or more mineral compositions selected from corundum, mullite, eucryptite, lithium aluminate, spodumene, spinel, zirconia, periclase, enstatite, and forsterite, and having a thermal expansion coefficient of 10×10 at room temperature to 1000° C. -6 / K or less and in the range of 1.0 to 2.0 times the thermal expansion coefficient of the main body, and the upper limit of the porosity is 50 volume %.

[0012] The method for manufacturing lightweight kiln furniture according to the present invention is a method for manufacturing lightweight kiln furniture consisting of a main body that contains or places a positive electrode material for a lithium ion secondary battery during heat treatment of the positive electrode material, and a protective layer that protects the main body from the positive electrode material, and is characterized by having a process for integrally molding the raw material mixture for the main body and the raw material mixture for the protective layer so that the protective layer is provided on at least the surface of the main body that contacts the positive electrode material, and a process for firing the molded body obtained by the integral molding at an atmospheric temperature of 1100 to 1400 ° C. Effect of the Invention

[0013] According to the present invention, it is possible to provide kiln furniture that is highly corrosion-resistant, strong, and lightweight, and is used in heat treatment of positive electrode materials for lithium-ion secondary batteries. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] Hereinafter, an embodiment of the lightweight kiln furniture of the present invention will be described. The lightweight kiln furniture of the embodiment of the present invention is composed of a main body made of a lightweight material that contains or places a positive electrode material for a lithium ion secondary battery during heat treatment of the positive electrode material, and a protective layer provided on at least the surface of the main body that contacts the positive electrode material, and the bulk specific gravity of the lightweight kiln furniture, which is obtained by dividing the mass W measured by a weighing scale by the volume V measured by a vernier caliper or the like (i.e., W / V), can be within the range of 0.5 to 1.5.

[0015] In order to improve corrosion resistance, it is preferable to use materials that have low reactivity with the positive electrode material to be fired for the main body and protective layer. Specifically, it is preferable to use one or more of ceramic powder, metal oxide, and metal salt that originally contain lithium components for each raw material. Furthermore, it is preferable that the raw material for the main body contains heat-resistant inorganic fibers and excipients in addition to the above raw materials.

[0016] As described below, the kiln furniture according to the embodiment of the present invention can be made lightweight because the porosity of the main body is large. Furthermore, it has excellent thermal shock resistance, strength, and thermal expansion properties. On the other hand, the raw material of the protective layer preferably contains an excipient in addition to the above-mentioned ceramic powder. Since the porosity of this protective layer is smaller than that of the main body, it is possible to further improve corrosion resistance. Furthermore, it has excellent thermal shock resistance, strength, and thermal expansion properties, and is less likely to peel off from the main body.

[0017] In the kiln tool according to the embodiment of the present invention, in order to increase the thermal shock resistance of the main body, the thermal expansion coefficient of the main body at room temperature (RT) to 1000°C is increased to 5×10 by adjusting the ratio of eucryptite, which has a negative thermal expansion coefficient, or spodumene, which has a small thermal expansion coefficient, or both, to one or more selected from lithium aluminate, spinel, zirconia, periclase, enstatite, forsterite, corundum, and mullite, which have a large thermal expansion coefficient. -6 / K or less, preferably 3.5×10 -6 / K or less. As mentioned above, the thermal expansion coefficient of the main body can be reduced to 5×10 -6By keeping it at or below 1 / K, the occurrence of cracks and other defects can be effectively prevented.

[0018] In addition, the kiln furniture of the embodiment of the present invention can have a thermal expansion coefficient ratio, obtained by dividing the thermal expansion coefficient of the protective layer by the thermal expansion coefficient of the main body, within the range of 1.0 to 2.0, preferably within the range of 1.0 to 1.4. That is, the kiln furniture of the embodiment of the present invention can have a thermal expansion coefficient of the protective layer of 10×10 -6 / K or less, preferably 7×10 -6 / K or less. By keeping the thermal expansion coefficient ratio within the above range, the thermal expansion coefficient of the protective layer becomes close to that of the main body, improving the adhesion of the protective layer to the surface of the main body and making it difficult for the protective layer to peel off from the main body. If the thermal expansion coefficient ratio exceeds 2.0, peeling of the protective layer may occur.

[0019] The upper limit of the porosity of the main body is 80% by volume, and a suitable upper limit is 60% by volume. If the porosity exceeds 80% by volume, the mechanical strength decreases and the shrinkage rate during firing increases, making the body more susceptible to deformation, which is undesirable. Conversely, the lower limit of the porosity of the main body is preferably 38% by volume, and more preferably 50% by volume. If the porosity of the main body is less than 38% by volume, the bulk density may exceed the desired upper limit.

[0020] On the other hand, the upper limit of the porosity of the protective layer is 50% by volume, and the preferred upper limit is 30% by volume. If the porosity exceeds 50% by volume, the corrosion resistance decreases. Conversely, the lower limit is preferably 15% by volume, and more preferably 20% by volume. If the porosity of the protective layer is less than 15% by volume, the thermal expansion coefficient may exceed the desired upper limit. The porosity can be increased or decreased by adjusting the particle size distribution and compounding ratio of the ceramic powder, heat-resistant inorganic fiber, and excipient used as raw materials, or by adjusting the pressing force during molding and the heat treatment conditions during firing.

[0021] The lightweight kiln furniture of the embodiment of the present invention can have a bending strength of preferably 3 MPa or more, more preferably 5 MPa or more, measured by carrying out a three-point bending test at room temperature with a test piece prepared in accordance with JIS R1601 supported at a span of 100 mm. If the bending strength is less than 3 MPa, the handling property is poor and the workability is also poor, which is not preferable. By setting the bulk density of the lightweight kiln furniture within the range of 0.5 to 1.5 as described above, the bending strength can be increased to a maximum of 22 MPa. In this way, the above bending strength can be adjusted mainly by the bulk density of the lightweight kiln furniture.

[0022] In an embodiment of the kiln furniture of the present invention, the main body preferably has a mineral composition containing 0 to 96 mass% mullite, 0 to 85 mass% corundum, 0 to 58 mass% eucryptite, 0 to 65 mass% lithium aluminate, 0 to 98 mass% spodumene, 0 to 82 mass% spinel, 0 to 78 mass% zirconia, 0 to 65 mass% periclase, 0 to 66 mass% enstatite, and 0 to 66 mass% forsterite.

[0023] In addition, in the kiln furniture of an embodiment of the present invention, the protective layer preferably has a mineral composition containing 0 to 99.5 mass% mullite, 0 to 99.5 mass% corundum, 0 to 58 mass% eucryptite, 0 to 93 mass% lithium aluminate, 0 to 99 mass% spodumene, 0 to 99.5 mass% spinel, 0 to 93.5 mass% zirconia, 0 to 87 mass% periclase, 0 to 90 mass% enstatite, and 0 to 90 mass% forsterite.

[0024] Next, an embodiment of a method for manufacturing a lightweight kiln tool according to the present invention will be described. As described above, one or more of ceramic powders, metal oxides, and metal salts that originally contain lithium are used as the raw materials for the main body and protective layer constituting the lightweight kiln tool according to the embodiment of the present invention. Among these, ceramic powders that originally contain lithium components include eucryptite, lithium aluminate, and spodumene. On the other hand, the above-mentioned metal oxides and metal salts include corundum, mullite, spinel, zirconia, periclase, enstatite, and forsterite. In the present invention, the ceramic powders, metal oxides, and metal salts that originally contain lithium components may be collectively referred to as ceramic powders. The ceramic powder is preferably blended so as to account for 15 to 98.5 mass% of the total raw materials for the main body, and is preferably blended so as to account for 70 to 99.5 mass% of the total raw materials for the protective layer.

[0025] The ceramic powder preferably has a median diameter (D50) in the range of 0.01 μm to 1 mm, more preferably in the range of 0.1 to 10 μm. If the median diameter is larger than 1 mm, the flowability of the raw material during the manufacture of kiln tools will be poor, and there is a high possibility that molding will not be possible. Conversely, if the median diameter is smaller than 0.01 μm, the raw material cost of the kiln tools will be too high. The median diameter (D50) refers to the particle size at 50% of the cumulative value in the volume-based particle size distribution determined by a laser diffraction particle size distribution analyzer.

[0026] In addition to the above ceramic powder, the heat-resistant inorganic fibers used as the raw material for the body are composed of one or more of alumina fibers (including mullite fibers), silica-alumina fibers, and biosoluble fibers of silica-magnesia-calcia system. These heat-resistant inorganic fibers have a heat-resistant temperature of 500°C or higher and 1600°C or lower, making them suitable as raw materials for the body of kiln tools. The heat-resistant temperature T°C refers to the case where the linear thermal shrinkage rate is 4.0% or less when heated in the form of a blanket at an atmospheric temperature T°C for 24 hours.

[0027] The heat-resistant inorganic fibers preferably have an average fiber diameter of 2 to 15 μm, more preferably 4 to 10 μm. Here, the average fiber diameter is obtained by photographing the fiber group to be measured with an electron microscope, measuring the width of any part of 200 fibers on the obtained image, and taking the arithmetic average. In addition, the heat-resistant inorganic fibers preferably have an average fiber length of 200 μm or more. However, if the fiber length exceeds 5000 μm, the fibers tend to be entangled with each other, making it difficult to mix uniformly, which leads to a decrease in moldability and the occurrence of cracks, so the upper limit of the average fiber length is preferably 5000 μm. Here, the average fiber length is obtained by photographing the fiber group to be measured with an electron microscope, measuring the linear distance from end to end in the longitudinal direction of any 100 fibers on the obtained image, and taking the arithmetic average.

[0028] Generally, heat-resistant inorganic fibers contain non-fibrous particles (shot) generated during the fiber manufacturing process, and 90% or more of the shot have a particle size of 45 μm or more. If a large amount of non-fibrous particles with such a large particle size are present, large pores are likely to be generated in the main body, resulting in reduced strength. Therefore, it is preferable that the content of non-fibrous particles relative to the total of heat-resistant inorganic fibers and non-fibrous particles is 10 mass% or less. The non-fibrous particle content here is determined by the measurement method of JIS R3311.

[0029] The heat-resistant inorganic fibers may be commercially available. For example, alumina fibers such as Arsen (registered trademark) manufactured by Denka Co., Ltd., mullite fibers such as Fibermax (registered trademark) manufactured by ITM Corporation and Maftec (product name) manufactured by Mitsubishi Chemical Corporation, silica-alumina fibers such as Isowool (product name) manufactured by Isolite Industries Co., Ltd., and biosoluble fibers such as silica-magnesia-calcia fibers such as Isowool BSSR1300 (product name) manufactured by Isolite Industries Co., Ltd. may be suitably used.

[0030] The heat-resistant inorganic fibers are preferably mixed so as to account for 1 to 60% by mass of the total raw materials of the main body. This allows them to function as aggregate in the main body, and the bending strength of the main body can be 3 MPa or more. If this content is less than 1% by mass, the bending strength of the main body may be less than 3 MPa. Conversely, if this content exceeds 60% by mass, it becomes difficult to achieve a bulk density of 0.5 or more for the kiln tools, and as a result, the porosity may be too high.

[0031] The above heat-resistant inorganic fibers have high tensile strength and tensile modulus, so they are unlikely to crack even when tensile force is applied by compressive force, and therefore the inclusion of the heat-resistant inorganic fibers in the main body has the effect of increasing mechanical strength. However, since the above heat-resistant inorganic fibers act to increase the porosity, they are not used as raw materials for the protective layer in order to prevent deterioration due to erosion by alkaline components such as lithium.

[0032] On the other hand, as mentioned above, the filler is used as both the raw material of the main body and the raw material of the protective layer. This filler is one or more of alumina fine particles (also called fumed alumina) and silica fine particles (also called fumed silica), and has a specific surface area of ​​60 m2 or less as measured by the BET method. 2 / g or more, and 2 / g or more is more preferable. In addition, the excipient is preferably made of nano-sized fine particles having a median diameter (D50) of about 1 to 100 nm.

[0033] The filler is preferably mixed so as to occupy 0.5-50% by mass of the total raw material of the main body, more preferably 10-30% by mass. If the mixing ratio is less than 0.5% by mass, the surface of each particle constituting the ceramic powder may not be sufficiently covered, and the desired strength may not be obtained. On the other hand, if the mixing ratio exceeds 50% by mass, the shrinkage rate during firing treatment becomes large, making the material more likely to deform, which is not preferable.

[0034] The filler is preferably mixed so as to occupy 0.5-30% by mass of the total raw material of the protective layer, more preferably 10-20% by mass. If the mixing ratio is less than 0.5% by mass, the surface of each particle constituting the ceramic powder may not be sufficiently covered, and the desired strength may not be obtained. On the other hand, if the mixing ratio exceeds 30% by mass, the shrinkage rate during firing treatment increases, making the material more likely to deform, which is not preferable.

[0035] For each of the raw materials for the main body and the protective layer, the ceramic powder, the heat-resistant inorganic fiber (only the raw materials for the main body), and the excipient are weighed out so as to obtain the above-mentioned blending ratio, and mixed preferably in a powder mixer equipped with an agitator (blade). During this mixing, a pore-imparting material may be added as necessary. As the pore-imparting material, an organic material consisting of one or more of cellulose, starch, and polyvinyl alcohol is preferably used. It is preferable to use a pore-imparting material having a median diameter (D50) of 100 μm or less. If the median diameter (D50) of the particle group of this pore-imparting material exceeds 100 μm, the fluidity of the raw materials decreases, making it difficult to mold the kiln furniture into the desired shape, and the porosity is likely to exceed the upper limit value mentioned above, which may result in insufficient strength of the lightweight kiln furniture.

[0036] The amount of the pore-imparting material added is preferably 100 parts by mass or less, more preferably 60 parts by mass or less, relative to 100 parts by mass of the total of the raw materials. If the amount added exceeds 100 parts by mass, the bulk density of the lightweight kiln furniture tends to be smaller than 0.5, which is the lower limit, and the strength of the lightweight kiln furniture may become insufficient, and the shrinkage rate during the firing treatment described below increases, making it more likely to deform, which is not preferable. There is no particular lower limit for the amount of the pore-imparting material added, but it is preferably 30 parts by mass or more relative to 100 parts by mass of the total of the raw materials.

[0037] During the above mixing, the rotation speed of the blade of the mixer is preferably 3000 rpm or more. This allows the heat-resistant inorganic fibers to be fully defibrated, so that the heat-resistant inorganic fibers can be dispersed almost uniformly in the above mixture in a state where they extend in random directions without being oriented in a specific direction. As a result, despite the bulk density being 1.5 or less, it is possible to obtain strength equal to or greater than that of conventional products with a bulk density of about 2.

[0038] The mixture obtained by the above mixing is then dry-pressed. In this pressurization, the conditions are appropriately adjusted so that the bulk density of the lightweight kiln ware, which is the fired product produced by the firing process in the next step, is within the range of 0.5 to 1.5. There is no particular limitation on the method for adjusting the conditions, and one example is a method in which the pressurization conditions during dry pressurization are determined based on a calibration curve showing the relationship between the pressurization conditions during past dry pressurization and the bulk density after firing of the molded body obtained by dry pressurization under those conditions.

[0039] The mixture obtained by mixing the above raw materials has a relatively small angle of repose and good fluidity, so that it is possible to mold lightweight kiln tools of complex shapes. In this pressure molding, the mixture of raw materials for the main body is first pressure molded to have the shape of a predetermined lightweight kiln tool, and then, of the molded body molded for the main body, at least the surface that will come into contact with the positive electrode material when used as kiln tool (for example, if the kiln tool is a sagger, its entire inner surface or its bottom) is preferably covered with the mixture of raw materials for the protective layer and molded integrally. Alternatively, the mixture of raw materials for the main body and the mixture of raw materials for the protective layer may be laminated in two layers, and then the two layers may be simultaneously pressed in the lamination direction to be molded integrally.

[0040] The compact thus obtained by dry pressure molding is placed in a heating furnace and sintered at an atmospheric temperature of 1100 to 1400°C. The atmosphere in the furnace during this sintering process is not particularly limited, but an air atmosphere is preferred. The sintering time is also not particularly limited, but about 2 to 5 hours is preferred. The sintering temperature is preferably adjusted appropriately within the range of 1100 to 1400°C depending on the type and content of the heat-resistant inorganic fiber and ceramic powder. This makes it possible to produce lightweight kiln furniture with a bulk density of 0.5 to 1.5, preferably 0.9 to 1.1. If the bulk density is less than 0.5, the lightweight kiln furniture may be insufficient in strength, and conversely, if the bulk density exceeds 1.5, the lightweight kiln furniture may be too heavy.

[0041] The thickness of the protective layer of the lightweight kiln furniture is preferably 0.5 to 5 mm, and more preferably 1 to 3 mm. If the thickness is less than 0.5 mm, it becomes difficult to perform integral molding during the dry pressure molding process in the previous process. On the other hand, if the thickness exceeds 5 mm, the mass of the protective layer becomes too large, causing the bulk density of the lightweight kiln furniture to exceed the upper limit of the range mentioned above, or cracks to appear with repeated use, which is not preferable. Generally, the thickness of the main body of the lightweight kiln furniture is about 5 to 20 mm.

[0042] As explained above, in the manufacturing method of lightweight kiln furniture according to the embodiment of the present invention, the molded body is formed by dry pressure molding, and therefore, unlike the molded body formed by the wet molding method, the heat-resistant inorganic fibers can be dispersed almost uniformly in a state of extending in random directions, as described above. That is, in the conventional wet molding method, a slurry prepared by adding an inorganic binder and an appropriate amount of water to a mixture is vacuum sucked or pressed to dehydrate it, and pressure molding is performed, so that the obtained molded body is likely to be layered in a state where the fiber groups extend in a direction approximately perpendicular to the suction direction, and directionality is likely to occur in the strength. In contrast, the molded body formed by the method according to the embodiment of the present invention has almost no directionality in its strength, so kiln furniture with high strength can be produced.

[0043] In addition, in the dry pressure molding, unlike the wet molding method, the excipient that plays the role of the inorganic binder can be used without agglomeration, so that the function can be fully exerted. Therefore, the desired strength can be secured even if the bulk density is small. In other words, in the wet molding method, the inorganic binder is aggregated to increase the yield, so the molded body itself tends to be formed from an aggregate of large-particle inorganic binder.

[0044] In addition, the wet molding method has a problem that the moldability is easily reduced when the amount of heat-resistant inorganic fiber is large, and when the molding is pressure-molded so that the bulk density of the molded body is small, sufficient strength cannot be obtained, but these problems are unlikely to occur in the method according to the embodiment of the present invention. Next, the present invention will be described in more detail with reference to examples, but the present invention is not limited to the following examples. EXAMPLES

[0045] [Example 1] A sagger as a lightweight kiln tool consisting of a roughly sake-cup-shaped main body and a protective layer provided on its bottom surface was produced using raw materials for the main body consisting of ceramic powder, heat-resistant inorganic fiber, and excipients, and raw materials for the protective layer consisting of ceramic powder and excipients, and its characteristics were measured. Specifically, the raw materials for the main body were weighed out so that the blend ratio was 55 mass% of spodumene powder (median diameter 23 μm) manufactured by Marusu Glaze Limited Liability Company as ceramic powder, 15 mass% of alumina fiber (Al2O3: 80 mass%, SiO2: 20 mass%) with an average fiber diameter of 4.0 μm and an average fiber length of 3.5 mm manufactured by Denka Co., Ltd. as heat-resistant inorganic fiber, and 30 mass% of fumed alumina (median diameter 100 nm) manufactured by Cabot Corporation as an excipient, and filled into a cylindrical container of a powder mixer having a shearing function. The mixture was mixed by rotating the blade at the bottom of the cylindrical container at 3000 rpm. The mixture was removed from the cylindrical container and placed in a mold, and compression molded from above to form a molded body that would become the main body of the sagger.

[0046] On the other hand, the raw materials for the protective layer were weighed out to have a blending ratio of 30 mass% of spodumene powder (median diameter 23 μm) manufactured by Marusu Glaze Co., Ltd. as a ceramic powder, 50 mass% of 8% yttria-stabilized zirconia powder (median diameter 15 μm) manufactured by Saint-Gobain Co., Ltd. as a ceramic powder, and 20 mass% of fumed silica (median diameter 50 nm) manufactured by Cabot Corporation as an excipient, and mixed under the same conditions as in the case of the main body. The resulting mixture was taken out of the cylindrical container, laminated so as to cover the bottom surface of the molded body that would become the main body, and then pressed to be integrally molded with the molded body that would become the main body. The sagger of Example 1 was produced by firing this integral molded body at an atmospheric temperature of 1100° C. for 3 hours.

[0047] [Examples 2 to 30, Comparative Examples 1 to 17] The saggers of Examples 2 to 30 and Comparative Examples 1 to 17 were produced in the same manner as in Example 1 above, except that the types of raw materials for the main body and protective layer, and their mixing ratios were variously changed, and the atmospheric temperature during the firing process was variously changed. In this case, in addition to the raw materials used in Example 1, the heat-resistant inorganic fibers used included mullite fiber manufactured by ITM Corporation (average fiber diameter 5.0 μm, average fiber length 3.0 mm, Al2O3: 72 mass%, SiO2: 28 mass%, non-fiber particle ratio 8 mass%), silica-alumina fiber manufactured by Isolite Industrial Co., Ltd. (product name Isowool 1260, Al2O3: 46 mass%, Al2O3 + SiO2: 99 mass%, average fiber diameter 4.2 μm, average fiber length 4.2 mm, fiber particle ratio 10 mass%), and biosoluble fiber manufactured by Isolite Industrial Co., Ltd. (product name Isowool BSSR1300, Al2O3: 77 mass%, CaO + MgO: 20 mass%, average fiber diameter 3.5 μm, average fiber length 4.5 mm, non-fiber particle ratio 10 mass%).

[0048] In addition to the raw materials used in Example 1, the ceramic powder used included eucryptite powder (median diameter 12 μm) manufactured by Marusu Glaze Limited Partnership Co., Ltd., lithium aluminate powder (median diameter 5 μm) manufactured by Kojundo Chemical Laboratory Co., Ltd., spinel powder (median diameter 22 μm) manufactured by Showa Denko K.K., magnesia powder (median diameter 13 μm) manufactured by Ube Materials Corporation, enstatite powder (median diameter 7 μm) manufactured by Asada Flour Milling Co., Ltd., forsterite powder (median diameter 5 μm) manufactured by Nissan Chemical Industries, Ltd., and alumina powder (median diameter 10 μm) manufactured by Sumitomo Chemical Co., Ltd. The blending ratios of the raw materials of the main body parts of Examples 1 to 30 and Comparative Examples 1 to 17 are shown in the following Table 1 (Examples) and Table 2 (Comparative Examples).

[0049] [Table 1]

[0050] [Table 2]

[0051] For each of the saggers of Examples 1 to 30 and Comparative Examples 1 to 17 prepared above, the bulk density and bending strength were measured, and the porosity, thermal expansion coefficient, and mineral composition of each of the main body and protective layer were also measured. Furthermore, the thickness of the protective layer on the cut surface of each kiln tool cut in half was measured using a vernier caliper. The bending strength was measured by a three-point bending test in accordance with JIS R1601. The bulk density and true density of each of the main body and protective layer taken from each kiln tool were measured, and then the porosity was calculated by "porosity = (1 - bulk density / true density) x 100". The thermal expansion coefficient was measured for each of the main body and protective layer taken from each kiln tool using a hot linear expansion measuring device (TD5000SE / H) manufactured by NETZSCH in accordance with JIS R2207-3 (Test method for thermal expansion of refractories - Part 3: Contact method using rod-shaped test pieces). The mineral composition of the main body and protective layer of each kiln tool was measured using an X-ray powder diffraction apparatus.

[0052] The corrosion resistance was evaluated by the following method. That is, 10 kg of a mixed powder in which lithium carbonate and cobalt oxide were mixed to have a molar ratio of Co:Li=1:1 was filled into each of the saggers of the above-mentioned Examples 1 to 30 and Comparative Examples 1 to 17, and the mixed powder was heat-treated by being charged into a heating furnace and heated to an atmospheric temperature of 950°C at a rate of 300°C / hr and held at the atmospheric temperature of 950°C for 10 hours. After the 10-hour holding period had elapsed, the saggers were forced to cool by introducing air into the heating furnace to lower the temperature to room temperature.

[0053] After the temperature drop, the mixed powder was taken out of the sagger and the presence or absence of damage to the inner surface of the sagger was visually observed. If no damage was found, the heat treatment of the mixed powder was repeated. In this manner, the corrosion resistance was evaluated based on the number of times the heat treatment was repeated until damage was found on the inner surface. The results of the evaluation of the corrosion resistance of each sagger, that is, the number of times the heat treatment was repeated until damage was found, are shown in Tables 3 to 10 below, together with the bulk density, bending strength, and thermal expansion coefficient ratio of the sagger, and the firing temperature during the firing treatment, as well as the porosity, thermal expansion coefficient, and mineral composition of each of the main body and protective layer.

[0054] [Table 3]

[0055] [Table 4]

[0056] [Table 5]

[0057] [Table 6]

[0058] [Table 7]

[0059] [Table 8]

[0060] [Table 9]

[0061] [Table 10]

[0062] As can be seen from Tables 3 to 7 above, all of the saggers of Examples 1 to 30 met the requirements of the present invention, and thus had a bending strength in the range of 3 to 22 MPa, despite their light weight of 0.5 to 1.5 in bulk density. In addition, the evaluation results of corrosion resistance were 12 times or more, and it was found that all of the saggers of Examples 1 to 30 had high corrosion resistance.

[0063] On the other hand, as can be seen from Tables 8 to 10 above, Comparative Example 1, in which the blending ratio of heat-resistant inorganic fibers in the raw materials for the main body was 61 mass%, had a porosity of the main body exceeding 80 volume%, so the bending strength was low at 2.5 MPa and the corrosion resistance was also poor. Comparative Example 2, in which the blending ratio of heat-resistant inorganic fibers in the raw materials for the main body was 0 (zero) mass%, so the bulk density was too high at 1.8. Comparative Example 3, in which the blending ratio of ceramic powder in the raw materials for the main body was 14 mass%, had a bulk density of 0.45, and the porosity of the main body exceeded 80 volume%, so the bending strength was low at 2 MPa and the corrosion resistance was also poor.

[0064] In Comparative Example 4, in which the blending ratio of ceramic powder among the raw materials for the main body was 99% by mass, the bulk density was 1.7, which was too large. In Comparative Example 5, in which the blending ratio of excipient among the raw materials for the main body was 0 (zero) mass%, the molding could not be performed well, so the production of the kiln tool was stopped midway. In Comparative Example 6, in which the blending ratio of excipient among the raw materials for the main body was 51% by mass, the porosity of the main body exceeded 80 volume %, so the bulk density was 0.47, the bending strength was low at 2.5 MPa, and the corrosion resistance was also poor. In Comparative Example 7, the bulk density was 1.8, which was too large. In addition, the combination of spodumene, which has a small thermal expansion coefficient, with one or more of lithium aluminate, spinel, zirconia, periclase, enstatite, forsterite, and corundum, which have large thermal expansion coefficients, was not appropriate, so the thermal expansion coefficient of the main body was 5.2 x 10 -6 / K.

[0065] In Comparative Example 8, the porosity of the main body was lower than the specified lower limit, so the bulk density exceeded 1.5. Conversely, in Comparative Example 9, the porosity of the main body exceeded the specified upper limit, so the bending strength was low at 0.7 MPa, and the corrosion resistance was also poor. In Comparative Example 10, the blending ratio of the ceramic powder contained in the raw material of the protective layer was 69 mass %, and the blending ratio of the excipient was 31 mass %, so the porosity greatly exceeded 50 volume %, and the corrosion resistance was poor. In Comparative Example 11, the porosity of the protective layer also exceeded 50 volume %, so the corrosion resistance was low. In Comparative Example 12, the thermal expansion coefficient ratio exceeded the upper limit of 2.0, so the corrosion resistance was low. In Comparative Example 13, the thermal expansion coefficient ratio exceeded the upper limit of 2.0, so the corrosion resistance was low, and furthermore, the thickness of the protective layer was thin at 0.4 mm, so the protective layer peeled off from the main body. In Comparative Examples 14 to 17, the thermal expansion coefficient of the protective layer was 10×10 -6 / K, resulting in reduced corrosion resistance.

Claims

1. A lightweight kiln tool having a bulk specific gravity of 0.5 to 1.5, the lightweight kiln tool being composed of a main body for accommodating or placing a positive electrode material for a lithium ion secondary battery during heat treatment of the positive electrode material, and a protective layer provided on at least the surface of the main body that contacts the positive electrode material, the main body having an upper limit of porosity of 80 volume %, the protective layer having one or more mineral compositions selected from corundum, mullite, eucryptite, lithium aluminate, spodumene, spinel, zirconia, periclase, enstatite, and forsterite, and having a thermal expansion coefficient of 10×10 at room temperature to 1000° C. -6 / K or less and within the range of 1.0 to 2.0 times the thermal expansion coefficient of the main body, and the upper limit of porosity is 50 volume %.

2. The main body has a mineral composition containing 0 to 96 mass% mullite, 0 to 85 mass% corundum, 0 to 58 mass% eucryptite, 0 to 65 mass% lithium aluminate, 0 to 98 mass% spodumene, 0 to 82 mass% spinel, 0 to 78 mass% zirconia, 0 to 65 mass% periclase, 0 to 66 mass% enstatite, and 0 to 66 mass% forsterite, and the protective layer contains 0 to 98 mass% mullite. 9.5% by mass, 0 to 99.5% by mass of corundum, 0 to 58% by mass of eucryptite, 0 to 93% by mass of lithium aluminate, 0 to 99% by mass of spodumene, 0 to 99.5% by mass of spinel, 0 to 93.5% by mass of zirconia, 0 to 87% by mass of periclase, 0 to 90% by mass of enstatite, and 0 to 90% by mass of forsterite.

3. The lightweight kiln furniture according to claim 1 or 2, characterized in that the bending strength of the lightweight kiln furniture is 3 to 22 MPa.

4. A lightweight kiln furniture according to any one of claims 1 to 3, characterized in that the main body has a lower limit of porosity of 38 volume %, and the protective layer has a lower limit of porosity of 20 volume %.

5. The lightweight kiln furniture according to any one of claims 1 to 4, characterized in that the protective layer has a thickness of 0.5 to 5 mm.

6. A method for manufacturing a lightweight kiln tool comprising a main body for accommodating or placing a positive electrode material for a lithium ion secondary battery during heat treatment of the positive electrode material, and a protective layer for protecting the main body from the positive electrode material, the method comprising the steps of: integrally molding the main body using a raw material mixture for the main body and a raw material mixture for the protective layer so that the protective layer is provided on at least a surface of the main body that contacts the positive electrode material; and firing the molded body obtained by the integral molding at an atmospheric temperature of 1100 to 1400°C; The raw material mixture of the main body contains 15 to 98.5 mass% in total of one or more of eucryptite, lithium aluminate, and spodumene as ceramic powders that inherently contain a lithium component, and one or more of corundum, mullite, spinel, zirconia, periclase, enstatite, and forsterite as metal oxides or metal salts, 1 to 60 mass% of one or more of alumina fibers and / or mullite fibers, silica-alumina fibers, and silica-magnesia-calcia-based biosoluble fibers as heat-resistant inorganic fibers, and alumina fine particles and silica fine particles as excipients. and one or more of the above are blended and mixed in an amount of 0.5 to 50 mass %, and the raw material mixture for the protective layer is blended and mixed in an amount of 70 to 99.5 mass % of eucryptite, lithium aluminate, and spodumene as ceramic powders that inherently contain a lithium component, and one or more of corundum, mullite, spinel, zirconia, periclase, enstatite, and forsterite as metal oxides or metal salts, and one or more of alumina fine particles and silica fine particles as excipients, and the raw material mixture for the protective layer is blended and mixed in an amount of 0.5 to 30 mass %.

Citation Information

Patent Citations

  • Roasting sagger for circulating type lithium battery anode material and preparation method thereof

    CN103311498A

  • Firing jig

    JP1998167840A

  • Calcination tool for electronic parts

    JP2002154884A

  • Sheath

    JP2011201762A

  • Ceramic coated sagger for producing lithium ion positive electrode active material

    JP2014118339A